A Comparison of Visual and Genetic Techniques for Identifying Japanese Marten Scats - Enabling Diet Examination in Relation to Seasonal Food Availability in a Sub-Alpine Area of Japan - Hisano, Masumi; Hoshino, Lisa; Kamada, Shouko; Masuda, Ryuichi; Newman, Chris; Kaneko, Yayoi (Zoological science, 2017)
We compared the reliability of visual diagnostic criteria to DNA diagnostic techniques, including newly designed primers, to discriminate Japanese marten (Martes melampus) feces from those of other sympatric carnivore species. Visual criteria proved > 95% reliable for fresh, odoriferous scats in good condition. Based upon this verification, we then examined if and how Japanese marten diet differs among seasons at high elevation study site (1500-2026 m). We also considered how intra-specific competition with the Japanese red fox (Vulpes vulpes japonica) may shape marten feeding ecology. From 120 Japanese marten fecal samples, high elevation diet comprised (frequency of occurrence) 30.6-66.0% mammals, 41.0-72.2% insects and 10.6-46.2% fruits, subject to seasonal variation, with a Shannon-Weaver index value of 2.77. These findings contrast substantially to seasonal marten diet reported in adjacent lowland regions (700-900 m), particularly in terms of fruit consumption, showing the trophic adaptability of the Japanese marten. We also noted a substantial dietary overlap with the red fox (n = 26 scats) with a Shannon-Weaver index of 2.61, inferring little trophic niche mutual exclusion (trophic niche overlap: 0.95), although some specific seasonal prey selection differences were likely related to relative differences in body size between foxes and martens. This additional information on the feeding ecology of the Japanese marten enables a better assessment of the specific risks populations face in mountainous regions.